Demarkációs vonalak Felvidéken, 1918 : (kartográfia-elemzés) = Lines of demarcation in Upper-Hungary, 1918 - Suba, János (Közép-Európai Közlemények, 2018)
The Czech and the Slovakian National Council had definite ideas about the boundaries of the future Czechoslovakian state. The Czech government was seeking to occupy the demanded territory before the decision of the peace conference. Masaryk, who was the President of the Czechoslovakian Republic, demanded the evacuation of Slovakia repeatedly. According to the Hungarian government, the occupation was not a political issue but the question of strategic expediency. That is why a Line of demarcation was created (between Bartha, minister of foreign affairs and Milan Hodza, Czech envoy). This Bartha–Hodza line of demarcation roughly followed the Northern geographical line of the Hungarian language border. The Hungarian government had an illusion that the final line of demarcation would be set by taking the temporary agreement into consideration. The president of the French military mission, Vix lieutenant-colonel, handed over the list on December the 24th, 1918 that defined the historical borders of the Slovakian land, behind which the Hungarian legions had to be ordered. This made the line(s) of demarcation that had been created earlier pointless. In addition, the Czech army did not cease its attacks afterwards, willing to occupy as big territories as possible.